THE ANALYSIS OF A COMPLEX COLLABORATIVE VALUE CHAIN. CASE OF AGROTRANSILVANIA CLUSTER - Felix H. ARION; Florina BARDEA; Diana C. CHIFOR; Lucian C. MAIER (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
A multifaceted and flexible partnership established to support the growth of the agro-industrial sector has produced the Value Chain of AgroTransilvania Cluster. Its goal is to aid in the growth of the association's and each member's competitiveness on both domestic and foreign markets. The aim of the article is to propose and set up an adequate strategy for assuring the common development of the AgroTransilvania Cluster. The analysis of internal and external ecosystem of the value chain of the AgroTransilvania Cluster – the material studied - was scrutinized using SWOT Analysis, used, aftercall, as groundwork for TOWS Matrix, completed by PESTEL analysis. The needs of the members of the cluster were identified using Delphi method, through questionnaires. The final result consists in a strategic planning document, so its implementation was assumed by the cluster’s members, assuring their involvement in joint, multi- and trans-disciplinary research, development, innovation, technology transfer, service provision, production, increasing visibility and not. The final aim of the strategy is to successfully generate the transition from an emerging cluster to an innovative one.